From "blessing in disguise" to "what do I do now?": How Canadian Olympic and Paralympic hopefuls perceived, experienced, and coped with the postponement of the Tokyo 2020 Games. (September 2022) - Bennett, Erica V.; Trainor, Lisa R.; Bundon, Andrea M.; Tremblay, Myriam; Mannella, Staci; Crocker, Peter R.E.
Abstract: The purpose of this study was to explore how Canadian elite athletes perceived, experienced, and coped with the Covid-19 pandemic and postponement of the Tokyo 2020 Games. We conducted semi-structured interviews with seven Paralympic and 14 Olympic hopefuls (n = 21). Data were analyzed using reflexive thematic analysis. Due to halting of training and competition and inabilities to live out the coveted performance narrative emphasizing winning above all, participants experienced complex emotional webs and questioned their purpose as athletes, which catalyzed psychological disruption. They coped by reframing the postponement as an opportunity for growth and risk-free chance to challenge the performance narrative through the embodiment of a reclaimed time narrative and associated attempts to diversify identities in non-sport domains. The findings highlight how the sociocultural environment impacts athletes' agency to self-regulate in response to unexpected and dynamic athletic career-related events, thereby prompting the negotiation of concomitant psychological (dis)stress and growth. Highlights: We explored how Canadian elite athletes responded to the postponement of Tokyo 2020 They experienced psychological disruption and questioned their purpose as athletes. Participants coped by reframing the postponed Games as an opportunity for growth. Athletes positioned the postponement as risk-free time to diversify identities. The performance narrative shaped and constrained athletes' agency to self-regulate.